Effects of Psychosomatic Mutual Aid Treatment on Anxiety and Depression in Turner Syndrome - Ye, Mudan; Lin, Huijia; Lash, Gendie E.; Yuan, Lianxiong; Li, Li (Frontiers in Psychiatry, 2021)
Background: Turner syndrome (TS) affects approximately one out of 2,500 females. Previous research indicates that girls with TS experience psychosocial impairment in addition to their physical health issues. However, there is no current data demonstrating whether reducing the clinical symptoms of girls or women with TS through hormone replacement therapy (HRT) combined with psychological interventions, referred to as psychosomatic mutual aid treatment (PMAT), improves physical and psychological self-identification, so that psychological problems such as anxiety, depression, low self-esteem, social loneliness, and psychological resilience are improved. Therefore, the objective of this research was to assess the efficacy of PMAT on anxiety and depression in girls and women with TS. Methods: Twenty-six girls and women with TS aged 11–29 years (17.5 ± 4.2 years) were recruited. Anxiety and depression were assessed using Hamilton Anxiety Rating Scale (HAMA) and Zung Self-Rating Depression Scale (SDS) questionnaires, respectively. The 26 TS patients were surveyed for anxiety and depression before the beginning of PMAT and again in January 2020. In addition, 20 healthy volunteer women aged 16–39 years (23.1 ± 5.7 years) were selected as the control group and filled in the questionnaire. Results: Pre-therapy (pre-HRT and Pre-PMAT) there were significant differences between the TS patients (n = 26) and healthy controls (n = 20). In particular, the TS patients had higher anxiety status (P = 0.04) and severity (P = 0.03) (HAMA score), as well as depression status (P = 0.002) and severity (P < 0.001) (SDS score). Post-therapy there was no longer any difference in depression scores, but TS patients still had higher levels of anxiety post-therapy compared with healthy control women (psychic symptoms score, P = 0.03; anxiety status score, P = 0.04; anxiety severity score, P = 0.04). In the TS patients, there was an improvement in depression scores (SDS score P < 0.001; depression severity score, P = 0.005) after therapy but no change in levels of anxiety. Conclusions: PMAT significantly improves depression status, but not anxiety, in girls and women with TS. Clinical Trial Registration:http://www.chictr.org.cn/showproj.aspx?proj=124736, identifier: ChiCTR2100045230.